Kelayakan Finansial PLTS Atap On-Grid pada Gedung Komersial - Eri Prabowo; Trassanda Scudetto Widestomo Putra; Theresia Margaretha Napitupulu (JTM : JURNAL TEKNIK MESIN, 2026)
This study evaluates the financial feasibility of an on-grid rooftop solar power plant implemented on a commercial building in West Java. The system is designed with a 50 kW inverter and 69 monocrystalline photovoltaic modules with a total array capacity of 34.5 kWp. The study applies a quantitative applied approach using load profile data, solar radiation data, investment cost, operation and maintenance cost, and electricity tariff as the main inputs. Financial feasibility is assessed using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period, while the technical contribution is evaluated through annual energy production and bill-saving potential. The rooftop PV system produces approximately 40,296 kWh per year and reduces monthly electricity consumption by about 3,358 kWh. This output provides a monthly saving of IDR 4,851,303 and an annual economic value of IDR 58,215,631 in the first year. With an initial investment of IDR 483,000,000 and inverter replacement considered in year 11, the project generates a positive NPV of IDR 111,294,381, IRR of 13.56%, and payback period of 9.07 years. These indicators show that the project is financially feasible and supports long-term operational cost efficiency, provided that system performance and maintenance are properly managed